Practice patterns of preoperative hormonal stimulation in pediatric penile surgeries—A survey of Nigerian pediatric surgeons. Issue 4 (August 2020) - Ezomike, U.O.; Nwangwu, E.I.; Chukwu, I.S.; Ekenze, S.O.
Summary: Background: Variable practice patterns exist in the use of Preoperative Hormonal Stimulation (PHS) prior to penile surgeries and there seems to be no generally agreed standards. Objective: To assess the current practice patterns of PHS before penile surgeries among Nigerian pediatric surgeons and compare with literature. Materials and methods: Self-administered questionnaires were distributed amongst consultants and senior registrars in Pediatric surgery during the 2019 Association of Pediatric Surgeons of Nigeria (APSON) national conference. SPSS version 20 was used for data entry and analysis and results presented as ranges, percentages, tables. Test for association was done using chi square test and a p-value of <0.05 was deemed significant. Results: All fifty respondents comprising 43 males, 7 females; 31 consultants and 19 senior registrars have managed hypospadias, with eighty-six percent managing less than 50 per year. Seventy-six percent practice PHS and more proportion of males use PHS than females (p = 0.027).Only 15.8% and 7.9% respectively estimated serum testosterone before and after PHS. Majority (92.1%) gave PHS because of small-appearing penis and 86.8% have used it in proximal hypospadias. Most commonly used form of PHS was intramuscular testosterone (76.3%) while 2 mg/kg testosterone was commonest dose (65.7%). Ninety-one percent give intramuscular testosterone at 2–4 weeks intervals; ninety-four percent give 2–3 doses of intramuscular testosterone preoperatively with last dose given 2–4 weeks before surgery in 57.9%. Ninety-two percent thought PHS will not increase postoperative complications and pubic hair was most common complication of PHS (63%). Discussion: There is diversity in PHS practices among Nigerian pediatric surgeons. Though mainly low-volume surgeons, majority use PHS before penile surgeries especially in proximal hypospadias and small-appearing penis. Males tend to practice PHS more than females and most commonly used form of PHS is 2–3 doses of 2 mg/kg intramuscular testosterone at 2–4 weekly intervals with last dose given 2–4 weeks before surgery. This study may be limited by bias inherent in self-reported practices and outcomes as seen in surveys, though surveys help to evaluate practices of professionals. Conclusions: Majority of Pediatric surgeons in Nigeria use PHS in form of intramuscular testosterone mainly for small appearing penis and proximal hypospadias. Most common dosing is 2 mg/kg at 2–4 weeks intervals and 2–3 doses preoperatively with the last dose 2–4 weeks preoperatively. Serum testosterone estimation is not common before PHS. Many believe that PHS does not increase complications following penile surgeries. Current diversity in practice suggests the need for further studies to encourage standardization or guidelines for practice in Nigeria . Summary Table Table showing the most prevalent responses Summary Table Variable Response Most common mean number of Hypospadias managed per month 1–2 Most common type of health Facility where pediatric surgeons work Tertiary Type of hypospadias where PHS most commonly used Proximal hypospadias Most commonly used form of PHS Intramuscular testosterone Most common interval between intramuscular testosterone injections 3 weeks Most common number of intramuscular testosterone doses before surgery Three Most commonly used dose of intramuscular testosterone. 2 mg/kg Most common duration between last dose of intramuscular testosterone and surgery Two to four weeks Most common observed side effects of PHS Pubic hair